ANALISIS PENGELOLAAN DANA DESA DALAM PENANGGULANGAN PANDEMI COVID-19 - Aldehin Banoet; Meyulinda A. Elim; Alfred T. Rantelobo (JAKA - Jurnal Jurusan Akuntasi, 2021)
Research on village fund management in tackling the Covid-19 pandemic (a case study in Kuanheun Village, West Kupang District, Kupang Regency, East Nusa Tenggara Province) aims to find out the process village fund management in the management of pandemic covid 19). This type of research uses a case study technique with a qualitative descriptive approach. The sample in this study amounted to 40 people consisting of village officials and the Kuanheun village community. Data collection was carried out by means of questionnaires, interviews and documentation which will be analyzed using qualitative descriptive methods in three stages, namely data reduction, data presentation, verification and conclusion. Based on the results of the analysis, it shows that the management of village funds at the budgeting stage has been carried out well but at the implementation stage and the accountability has not been fully carried out properly because at the implementation stage there are still activities which is not implemented according to what has been determined and at the accountability stage there is still no report made such as the first semester Realization of the Use of Village Funds Report